Electronic properties of zigzag silicene nanoribbons with single vacancy defect - Mu Wen Chuan; Kien Liong Wong; Afiq Hamzah; Nurul Ezaila Alias; Cheng Siong Lim; Michael Loong Peng Tan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Silicene is envisaged as one of the two-dimensional (2D) materials for future nanoelectronic applications. In addition to its extraordinary electronic properties, it is predicted to be compatible with the silicon (Si) fabrication technology. By using nearest neighbour tight-binding (NNTB) approach, the electronic properties of zigzag silicene nanoribbons (ZSiNRs) with single vacancy (SV) defects are modelled and simulated. For 4-ZSiNR with L=2, the band structures and density of states (DOS) are computed based on SV incorporated ZSiNRs at varying defect locations. The results show that the SV defect will shift the band structure and increase the peak of DOS while the bandgap remain zero. This work provides a theoretical framework to understand the impact of SV defect which is an inevitable non-ideal effect during the fabrication of silicene nanoribbons (SiNRs).